1981
DOI: 10.1002/j.1875-9114.1981.tb03562.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol: A Review of Its Pharmacology, Pharmacokinetics, Adverse Reactions, and Clinical Use

Abstract: Glycerol is a potent osmotic dehydrating agent with additional effects on brain metabolism. In doses of 0.25-2.0 g/kg glycerol decreases intracranial pressure in numerous disease states, including Reye's syndrome, stroke, encephalitis, meningitis, pseudotumor cerebri, central nervous system tumor, and space occupying lesions. It is also effective in lowering intraocular pressure in glaucoma and shrinking the brain during neurosurgical procedures. Hyperosmolality with rebound cerebral overhydration is of concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
82
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 68 publications
1
82
0
1
Order By: Relevance
“…Considering that the intestinal absorption of glycerol, a potent oral osmotic dehydrating agent for the treatment of glaucoma, is highly efficient 3) and that glycerol is a nutritional component that can be liberated from dietary fat (triglycerides) in the intestinal tract, 4,5) it is possible that a carrier-mediated transport system is involved in the efficient absorption and utilization of this nutritional substance. Therefore, to further confirm the suggestion from our earlier studies and clarify the physiological relevance, we examined the absorption of glycerol using the closed loop of the rat small intestine in situ.…”
mentioning
confidence: 99%
“…Considering that the intestinal absorption of glycerol, a potent oral osmotic dehydrating agent for the treatment of glaucoma, is highly efficient 3) and that glycerol is a nutritional component that can be liberated from dietary fat (triglycerides) in the intestinal tract, 4,5) it is possible that a carrier-mediated transport system is involved in the efficient absorption and utilization of this nutritional substance. Therefore, to further confirm the suggestion from our earlier studies and clarify the physiological relevance, we examined the absorption of glycerol using the closed loop of the rat small intestine in situ.…”
mentioning
confidence: 99%
“…We also found an earlier report suggesting carrier-mediated glycerol transport in the rabbit small intestine, 2) in agreement with our own finding. Considering that the intestinal absorption of glycerol, which is a potent oral osmotic dehydrating agent for the treatment of glaucoma, is highly efficient 3) and that glycerol is a nutritional component that can be liberated from dietary fat (triglycerides) in the intestinal tract, 4,5) it is possible that a carrier-mediated transport system is involved in the efficient absorption and utilization of this nutritional substance.…”
mentioning
confidence: 99%
“…A two-to three-fold intersubject variation in GLY clearance has 20 been reported for humans (Frank et al 1981). Riedesel et al (1987) found that sGLY concentrations had decreased by only 29% (4.3 mM) four hours After ingesting the GLY solution.…”
Section: Serum Netabolitesmentioning
confidence: 91%
“…Peak sGLY concentrations are reported to occur within 60 to 90 minutes following ingestion (Frank et al 1981).…”
Section: Serum Netabolitesmentioning
confidence: 99%